Multidecadal biogeomorphic dynamics of a deltaic mangrove forest in Costa Rica - Acuña Piedra, Jéssica Francini (2021)
Térraba-Sierpe National Wetland (TSNW) is the largest wetland in Costa Rica located in the southeastern part of the country. The protected area comprises the Térraba-Sierpe delta covered with dense mangrove vegetation. We aim to analyze the geomorphological evolution of the coastal bars and the land use/cover chéange between 1948 and 2012 using aerial photographs and satellite images interpretation as well as field corroboration. We determined the geomorphological dynamics of three coastal bars (supratidal, intertidl, and subtidal), ten land uses/covers, and deforestation rates of six delta mouths for 64 years. In addition, we estimated a net periodic loss by deforestation between 1948 and 2012 exceeding 2562 ha, with an annual net loss of 40 ha per year. Moreover, these outputs quantify the anthropic impact over 40 years and give good evidence from an example of environmental policies implementation since the 1990s to protect these fragile tropical ecosystems.